Chinese English as a Foreign Language Teachers’ Job Satisfaction, Resilience, and Their Psychological Well-Being - Han, Wenjing (Frontiers in Psychology, 2022)
Job satisfaction, resilience, and teacher well-being might be important factors in improving the quality of education. Recently, these notions have received special attention among English as a foreign language researchers; therefore, this particular study investigated the relationship between Chinese EFL teachers’ job satisfaction, resilience, and their well-being. To conduct the study, 343 Chinese EFL teachers with different academic qualifications, various academic degrees, and different majors voluntarily participated in this study. The results of the study showed that job satisfaction and resilience could jointly predict 56.4 of the variance in psychological well-being. Both variables were the significant predictor of well-being, while satisfaction was a better predictor, uniquely explaining 29.6 of well-being’s variance. The findings suggested that principals play a significant role in increasing teachers’ satisfaction, resilience, and as a consequence teachers’ well-being.